The utility of caffeine citrate as a neuroprotectant in the early life of premature newborns: a literature review of the effects on neurodevelopmental outcomes - Phung, Lauren; Duong, Kaithlyn; Obeid, Rawad (Frontiers in Pediatrics, 2025)
The incidence of prematurity-related complications has decreased due to advancements in medical preventive and supportive measures, but the rate of neurodevelopmental impairment secondary to prematurity continues to increase. Due to the high metabolic demand of the central nervous system during early development and the age-related sensitivity of the cerebral white matter, perinatal intermittent hypoxia can lead to significant cerebral pathology persisting into adulthood. Caffeine citrate is one of the mainstay medical treatments for apnea of prematurity and is widely used in many neonatal intensive care units. Caffeine citrate's benefits include reducing time on mechanical ventilation, enhancing extubation success, and decreasing the incidence of bronchopulmonary dysplasia. There is also mounting evidence that caffeine citrate benefits neurodevelopmental outcomes, attributable to its positive effect on respiratory status and other mechanisms. Research has shown that caffeine citrate exerts an anti-inflammatory effect via the antagonism of adenosine receptors, reduces the production of reactive oxygen species, and supports the plasticity of the central nervous system. This article aims to review the most up-to-date evidence on caffeine citrate's effects on neuroprotection and its role in reducing the severity of neurodevelopmental impairment associated with prematurity.